Excessive tooth wear on human dental enamel: a case report - Ramos Braga Santos, Sara; Vieira Bittencourt, Marcos Alan (Revista de Ciências Médicas e Biológicas, 2022)
Introduction: although reports on dental erosion have appeared in literature for a long time, there is currently a growing interest among researchers and clinicians about this matter. Potential risk factors for loss of dental hard tissue are changed lifestyle and eating patterns, with increased consumption of acid foods and beverages. Case report: an atypical tooth wear on the buccal surfaces of the mandibular teeth in a 45-year-old woman referred for orthodontic treatment, associated with the frequent consumption of whiskey and lemon, is reported. A comprehensive approach, such as the recognition of dental erosion joined with a careful investigation about eating habits was performed. Ultrastructural examination of replicas of the teeth showed practically structureless enamel and dentin surfaces. Conclusion: the screening for dental erosion in patients seeking orthodontic treatment is advisable to be a usual procedure. Recommendations for treatment and prophylactic measures are made emphasizing the need of multiprofessional attention.